MODULAR DATA CENTER FOR SCIENTIFIC DATA PROCESSING - Isaev, E. A.; Lusakov, S. V.; Amzarakov, M. B.; Suhov, R. R.; Isaev, K. A. (Одеські астрономічні публікації, 2013)
In mid-2000 there were the first mobile (containerized) data centers. The need to rapidly deliver IT infrastructure was partly satisfied by similar solutions. Stage by stage growth was implemented into a classical data centers even earlier. Modular data center brought together the benefits of mobility and maximum flexibility in the stage by stage of capacity growth. In this paper, shows the specificity of modular processing centers of scientific data and provides relevant examples of such data centers.